2017
DOI: 10.1161/circulationaha.116.026687
|View full text |Cite
|
Sign up to set email alerts
|

Systolic Blood Pressure Trajectory, Frailty, and All-Cause Mortality >80 Years of Age

Abstract: BACKGROUND:Clinical trials show benefit from lowering systolic blood pressure (SBP) in people ≥80 years of age, but nonrandomized epidemiological studies suggest lower SBP may be associated with higher mortality. This study aimed to evaluate associations of SBP with allcause mortality by frailty category >80 years of age and to evaluate SBP trajectories before death. METHODS:A population-based cohort study was conducted using electronic health records of 144 403 participants ≥80 years of age registered with fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
120
3
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(135 citation statements)
references
References 48 publications
7
120
3
5
Order By: Relevance
“…A recent observational cohort study that tracked SBP trajectories for the 5 years before death in 144,403 individuals aged 80 older provides a compelling example of this limitation. 9 Consistent with Wu and colleagues and other observational studies, mortality was greatest in those with SBP less than 110 mmHg, although there was a decline in the SBP trajectory noted in the last 3 months of life in individuals undergoing treatment for hypertension and those not undergoing treatment. This terminal decline in SBP provided the best explanation for the observed association between low SBP and mortality in this and probably other observational studies.…”
supporting
confidence: 83%
“…A recent observational cohort study that tracked SBP trajectories for the 5 years before death in 144,403 individuals aged 80 older provides a compelling example of this limitation. 9 Consistent with Wu and colleagues and other observational studies, mortality was greatest in those with SBP less than 110 mmHg, although there was a decline in the SBP trajectory noted in the last 3 months of life in individuals undergoing treatment for hypertension and those not undergoing treatment. This terminal decline in SBP provided the best explanation for the observed association between low SBP and mortality in this and probably other observational studies.…”
supporting
confidence: 83%
“…11 In the latter regard, a recently reported United Kingdom population-based cohort study in 144 403 subjects aged >80 years demonstrated a significant association between lower SBP and all-cause mortality, independent of frailty status. 12 The association appeared to be explained, in part, by a terminal decline in SBP in the final 2 years of life. The investigators concluded that reverse causation might have pertained if lower SBP resulted from temporal proximity to death and that the observed (nonrandomized) association between higher SBP O'Gara BP, Arterial Load, and Survival After TAVR and greater longevity could have been confounded.…”
Section: See Article By Lindman Et Almentioning
confidence: 99%
“…12 A single blood pressure determination in elderly patients 30 days after TAVR may not provide enough information from which to draw firm conclusions on causality.…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations